Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.21767/2471-9641.100023
|View full text |Cite
|
Sign up to set email alerts
|

The Propolis Effect on Chlorpyrifos Induced Thyroid Toxicity in Male Albino Rats

Abstract: Chlorpyrifos (CPF) is a chlorinated organophosphate insecticide that is used widely in the world and Egypt. The aim of present work was to study the possible protective role of Propolis on thyroid gland of male rats after chronic exposure of chlorpyrifos. For this purpose, Fifty adult male albino rats were randomized into 5 groups: I, II (Control), III (received Propolis dissolved in 0.5 ml corn oil, 50 mg/kg b.w./day), IV (received CPF dissolved in 0.5 ml corn oil 6.75 mg/kg b.w./ day) and V (received CPF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that chlorpyrifos insecticide-treated rats demonstrated hypothyroidism, which was confirmed biochemically by huge declinein serum T3 and T4 levels and histologically by a diminished measureof colloid. Furthermore, chlorpyrifos cause a decrease of PAS response in the colloid and is revealed immunohistochemically by a weak thyroglobulin protein expression in the colloid [ 29 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that chlorpyrifos insecticide-treated rats demonstrated hypothyroidism, which was confirmed biochemically by huge declinein serum T3 and T4 levels and histologically by a diminished measureof colloid. Furthermore, chlorpyrifos cause a decrease of PAS response in the colloid and is revealed immunohistochemically by a weak thyroglobulin protein expression in the colloid [ 29 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also Kassab and El-Aasr found that chlorpyrifos induced follicular cell degeneration, collagen fibers deposition and decreased colloid secretions (19) .Similarly, another study on the effect of chlorpyrifos on female wistar rats concluded that short term daily intake of low and high doses of chlorpyrifos induced a significant thyroid hormone level disrupting effects (20) .Other authors found that chlorpyrifos reduced antioxidant enzyme activities and glutathione (GSH) in the thyroid gland tissues. Moreover; it elevated the level of malondialdehyde (9) .In the same line Abed and Alkalby (21) found a destruction of thyroid follicles with infiltration of macrophages and a significant elevation in serum level TSH and a significant reduction in (T4) and (T3) hormones compared to the control group. The chlorpyrifos toxic effects on the thyroid gland tissue may be due to lipid peroxidation that associated with stimulation of stellate cells for collagen synthesis in between thyroid follicles (18) .Another study revealed that the toxic effect of chlorpyrifos may be due to decreased the iodine binding proteins (22) and Wang et al stated that organophosphate exposure associated with changes in the thyroid gland function in pregnant women (23) .…”
Section: Discussionmentioning
confidence: 70%
“…Group II (CPF group): rats were given CPF dissolved in 0.5 ml corn oil at a dose of 6.7 mg/kg b.w. five days / week for six weeks (9) Group III (ginger extract-treated group): rats were given CPF and ginger extract at a dose of 750 mg/kg b.w. five days / week for six weeks (10) Group IV (selenium-treated group): rats were given CPF and sodium selenite at a dose of 10 µg/Kg b.w five days / week for six weeks (11) Blood samples were taken from the retro orbital venous plexuses for hormonal assay, then rats were anaesthetized by ether inhalation.…”
Section: Drugsmentioning
confidence: 99%
“…Previous studies suggested that the insecticide-induced disturbance in the thyroid hormones level may be the result of increased hepatic enzyme activity (Al-Amoudi, 2018) or the consequence of oxidative stress in the central nervous system and its related glands, including the hypothalamicpituitary axis, which may be one of the most important factors in the general ageing process. The ageing of the hypothalamic-pituitary axis leads to progressive functional loss and gradually develops into endocrine deficiency (El-sheikh and Ibrahim, 2017).…”
Section: Evaluation Of Hormonal Parametersmentioning
confidence: 99%